Hitler's war 1942-1945 - Irving, David (East Ardsley, Wakefiield, West Yorkshire, England : EP Microform Ltd., 1977)
Reproduces personal correspondence, diaries and transcripts and other documentation, as well as some material on the Jewish problem in Germany.
Contents of reels available online at publisher's Web site.
jakir
Keywords: World War, 1939-1945 -- Germany -- Sources; Germany -- Armed Forces -- History -- 20th century -- Sources; Germany -- History -- 1933-1945 -- Sources